1996
DOI: 10.1051/jp4:1996548
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Efficiency Enhancement in Microchannel Plate Detectors

Abstract: Abstract. The detection efficiency of a channel-plate detector is mainly determined by the open area ratio of its input face. which is typically 60%-70%. It is known that the efficiency can be enhanced by applying an electric field normal to the channel-plate surface, such that secondary electrons generated when ions strike the channel-plate surface are returned to the detector. This paper characterises the enhancement observed in channel-plate detectors for atom probe and 3-dimensional atom probe applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Studies of precipitation phenomena, grain boundary segregation, and long-range ordering in materials have shown the ability of this instrument to give quantitative materials chemistry results on the nanometer scale. Some recent work has shown that it is possible to increase detection efficiency up to 86% (Deconihout et al, 1995b;Sijbrandij et al, 1996a). The main issue concerns the mass resolution of the instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of precipitation phenomena, grain boundary segregation, and long-range ordering in materials have shown the ability of this instrument to give quantitative materials chemistry results on the nanometer scale. Some recent work has shown that it is possible to increase detection efficiency up to 86% (Deconihout et al, 1995b;Sijbrandij et al, 1996a). The main issue concerns the mass resolution of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it appears that the low detection efficiency makes impossible the study of the earliest stages of ordering phenomena. Some recent work has shown that it is possible to increase detection efficiency up to 86% (Deconihout et al, 1995b;Sijbrandij et al, 1996a). As a result, the number of positioned atoms in 3-D images can be increased by approximately 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to exceed the OAR limit have been made by applying a repelling electric field to reflect secondary electrons back to the MCP surface. 3,17,[19][20][21][22] An essential solution would be to widen the open area. An efficient way to accomplish this goal is to narrow the walls of the pores.…”
Section: Introductionmentioning
confidence: 99%
“…This causes secondary electrons generated when ions strike the area between the channels to be returned towards the detector. Detection of these electrons increases the efficiency of the detector above the open area ratio of the channel plate (65%) to approximately 80% [6]. Previously, 3DAP instruments have been based around a straight flight path configuration, such that their mass resolution has been limited by ion energy variations to n~/Am=100-200 full width at half maximum (FWHM).…”
Section: Introductionmentioning
confidence: 99%